The Effectiveness of Using Picture Series as Media to Teach Writing Procedure Text for Tenth Graders of SMA NegeriBandarkedungmulyoJombang (RETAIN, 2014)
The Effectiveness of Using Picture Series as Media to Teach Writing Procedure Text for Tenth Graders of SMA NegeriBandarkedungmulyoJombang Mochammad Riyan English Education, Faculty of Languages and Arts, State University of Surabaya Mochammadriyan347@gmail.com Fauris Zuhri, S.Pd., M.Hum. English Education, Faculty of Languages and Arts, State University of Surabaya Abstract Some people may find difficulties in writing something or express their ideas. They have a lot of ideas in their mind, but they cannot decide what they want to write. When the first problem solved, other problem appear that they do not know how to write correctly. Those difficulties faced by students, too and make them frustated and not confident in writing. The teacher has a job to give some stimulus and let the students’ imagination free by not forcing the students directly to write and not giving them the same boring strategy all the time. The teacher can use Picture Series. The use of picture series can help the students to be more interested in the material and it is makes students easier to write down their own concept. The research is an experimental research and the objective of this study To find out whether there is significant effect between the students who have been taught writing using picture series and students who have not. The subject of this research was the tenth grade students of SMA Negeri BandarkedungmulyoJombang which consisted of 2 classes, X IPS 1 (28 students) and X IPS 2 (30 students). The research instrument, the researcher uses test as the research instrument. The researcher find that picture series was easy to use so they could write with picture series easily. Writing procedure through picture series brought the students to new kind of situation. It would help both the teacher and students to revise the students’ writing and made writing more fun than the way it used to be. Keywords: Picture series, writing, procedure text. Abstrak Beberapa orang mungkinmengalamikesulitandalammenulissesuatuataumengekspresikan ide-ide mereka. Merekamemilikibanyak ide dipikiranmereka, tetapimerekatidakdapatmemutuskanapa yang akanmerekatulis. Ketikamasalahpertamaterpecahkan, masalah yang lain munculbahwamerekatidaktahubagaimanacaramenulisdenganbenar. Kesulitan-kesulitanitudihadapijugaolehmurid-muriddanmembuatmerekafrustasidantidakpercayadiridalammenulis. Seorang guru mempunyaitugasuntukmemberikanbeberapa stimulus danmembiarkan para muridbebasuntukberimajinasidengantidakmemaksamerekauntukmenulissecaralangsungdantidakmemberikanmerekastrategi yang membosankansetiapsaat. Seorang guru dapatmenggunakanpicture series. Penggunaanpicture series dapatmembantumurid-muriduntuklebihtertarikdenganpelajarandanpicture seriesmembuatmurid-muridlebihmudahuntukmenulis ide merekasendiri. Penelitianinimerupakanpenelitianeksperimentaldantujuandaripenelitiainiadalahuntukmenemukanapakahadaperbedaan yang signifikanantaramurid-murid yang menulisdenganmenggunakanpicture seriesdanmurid-murid yang yangmenulistanpamenggunakanpicture series. Subjekdaripenelitianiniadalahmurid-muridkelas 10 SMA NegeriBandarkedungmulyoJombang yang terdiridari 2 kelas, X IPS 1 (28 murid) dan X IPS 2 (30 murid). Penelitimenggunakan test sebagaiinstrumenpenelitian. Penelitimenemukanbahwapicture series mudahuntukdigunakanjadimerekadapatmenulisdenganmudahmenggunakanpicture series. Menulisprosedurteksmelaluipicture series membawamurid-muridkepadasituasi yang baru. Ituakanmembantu guru danjugamuriduntukmerevisitulisanmurid-muriddanmembuatkegiatanmenulislebihmenyenangkandaripadaseharusnya. Kata kunci: picture series, menulis, prosedurteks. INTRODUCTION English has four basic skills (listening, speaking, reading, and writing) that every skill is related to each other. Four of the skills should be mastered by the students to increase their ability in English learning. Writing has important role for students to learn English. Writing involves language components such as grammar, vocabulary, and pronunciation. Based on Braine and Claire May (1991:60) state “writing clear sentence requires you to learn the rules of English grammar and mechanics such as the correct use of verbs and pronouns, as well as commas and other marks of punctuation”. Myles (2002:15) states that writing is an English skill which needs an effort and much practice in composing, developing, and analyzing ideas. Writing is considered as a complicated skill for the students and the teachers. Chastian (1988:221) stated that writing and speaking are difficult skills to acquire because the students must have a more complete control of the elements of language, such as vocabulary, sentence, or grammar. It means that the students have to combine the elements of writing including content, organization, vocabulary, grammar, and mechanic when they want to write. In education world, writing is an important thing for students, Hyland (2003:20) states that the important reason for teaching writing for students is because writing helps students to learn. Fellag (2004:10) states that writing consist of steps that you may need to repeat as you write are getting ideas, organizing your ideas, writing your first draft, revising to improve content and organization, and editing for language errors. There are many kinds of texts that can be used by students as their writing materials. One of them is procedure text. Procedure text is a text that is designed to describe how something is achieved through a sequence of actions or steps. In teaching learning activity, writing procedure text should be interesting for student but in fact, the students just feel bored with the lesson. This kind of situation will be happened when the teacher cannot explain the materials in right ways. The teacher cannot show media related to the topic. To solve these problems, the teachers must realize that they need to use appropriate teaching media to improve students’ writing scores. There are many kinds of media that can be used such as picture, maps, real things, dialogue and tables present the materials (Bryne, 1991:17). One of the effective ways to help the students in learn how to write procedure text is using picture series. Picture series are the picture that tell a story in a sequence on a one chart (Finocchiaro, 1974:100). In other side, picture series can help the students to create or produce a procedure text by showing some pictures that related with the topic. It can develop their imagination and open their mind about how to make or produce something. Students can construct their knowledge during learning procedure text easily by using media. One of the media is picture series which draws a story. Picture series is several or sequence events, actions or steps that come in photographic representation of people, places, and things and happened one after the other. This medium fulfills the principles of using media issued by Nyoman S. Degeng (2001). Media which can be used to make the students learn more easily and the teacher teaches easily is the main part of the learning process. The media must be used in integrated way in teaching and learning and not only as ice breaker of teaching and learning. In addition, Wright (1997) stated that picture series are pictures, which show some action or event in chronological order. According to him, picture series can be used to depict a process how to make something. Hammer (2004) adds that pictures are often used to present situation to help the students work with grammar and vocabulary. To understand the way of the picture series, the students need to appreciate it in abstract way. In the same way, when they express their ideas to construct the text in a good coherence as well as unity, they have to think it in abstract way too. Both of them will be easier for them in learning process if the teacher can use picture series. It can not only help the students to get ideas more realistic in understanding the procedure text but also in constructing ideas to create it. Wright (1997) states that picture can play a key role in motivating students, conceptualizing the language they want to use and giving them a reference. Based on those explanations above, this research has been set to find out whether there is significant effect between the students who are taught by using picture series and those who are taught without picture series. METHOD This research is experimental research to find out whether there is difference between the students writing score which are taught using picture series and which are taught without picture series. The design employs two groups, experimental and control groups. This research will be held in two weeks, four meetings for both groups. Both of group will be given pre-test and post-test. The pre-test is given at the beginning of the study in order to find out the students ability in composing procedure text. Then, the treatment will be given for experimental group only. In the last meeting, both groups will be given a post-test to find out the difference between the two groups as the effect of the treatment. The subject of this research is the first year’s students of SMA NegeriBandarkedungmulyoJombang. The researcher will choose two classes as experimental and control group. Two classes are taken randomly from the whole classes in SMA NegeriBandarkedungmulyoJombang; those two classes are X IPS 1 and X IPS 2. X IPS 1 is taken as a control group of the study and X IPS 2 is taken as an experimental group of the study. In this research, the researcher using pre-test and post-test as the instrument. The test is in the form of writing test of procedure text. The test is conducted before the treatment as a pre-test and after the treatment as a post-test. The teacher asks the students to make a procedure text. The researcher collected the data by pre-test and post-test. Pre-test for control group (X IPS 1) was conducted on December 11th 2013 and pre-test for experimental group (X IPS 2) was conducted on December 12th 2013. Before the test was given to the students, it was tried out in different school but in same level. When the test was considered to be valid, it is used as pre-test and post-test for both groups. The second step was treatment for experimental group only on December 16th 2013. On the other hand, the control group will be taught, in the old way without using picture series and it was applied on December 14th 2013. Finally, the post-test for experimental group was conducted on December 18th 2013 and post-test for control group was conducted on December 17th 2013. In this case, the test in pre-test and post-test are the same. The next step is compute the result by using t-test formula to calculate the t-value of pre-test and post-test of both experimental and control groups. The t-test was used to know whether there was a significant difference between experimental and control group, the used of t-table was as a comparison if the result of the t-test was higher it means that there was significant difference between two groups meanwhile if the t-test was lower than the result of the t-table means that there was no significant difference between two groups. RESULTS AND DISCUSSION This experimental research was conducted to find out whether there is a significance difference between the students’ who are taught procedure text by using Picture Series and those who are taught procedure text without Picture Series. There were two steps to obtain the data, first the researcher used pre-test to both experimental and control groups this was conducted in order to know the students’ writing ability before given treatments. The last step was post-test this was conducted to both experimental and control groups in order to know if there is any significance difference in students’ writing ability after given treatments. There were some procedures to calculate the data between pre-test and post-test, the procedures were same between those two groups. First procedure was finding the mean, second procedure was finding the standard deviations, third procedure was finding standard error of difference, and the last procedure was calculate t-value by using t-test formula. The researcher conducted the pre-test in order to know the students’ writing ability before given treatments. the score and mean of control group was higher than experimental group. The score of control group was 1855 and the mean was 66.25 while the score of experimental group was 1915 and the mean was 63.83. However, that indicated that those two groups had equal ability in writing procedure text before the treatment was given in the other word they were not siqnificantly different in writing ability. After the pre-test was conducted to both groups, the researcher applied the Picture Series as media to teach writing procedure text for experimental group, while the control group got treatments without using Picture Series. Post-test was administered after the researcher had done the treatments; the test was same as in pre-test with the same topic. The score and mean of experimental group was higher than control group. The score of experimental group was 2385 and control group was 2055. It was definitely clear that the mean of experimental group also higher than control group, the mean of experimental group was 79.5 and control group was 73.39. It was clearly seen that there was an improvement in students’ writing ability of experimental group, it was happened because the experimental group had been given the treatments by using Picture Series. The next step is calculating the standard deviation of both groups. The standard deviation of control group was higher than experimental group. The standard deviation of control group was 7.59 and experimental group was 5.96. In this step the researcher could not conclude whether there is significant difference or not because this was not final calculation. Next step calculated standard error of the difference of both experimental and control group. The calculation of standard error of the difference between experimental and control group was gained from the result of standard deviations of both experimental and control group and the result presented that the standard error of the difference between experimental and control group was 1.82. As the final calculation, then the researcher calculated the t-value by using t-test formula The researcher used t-test formula to calculate the t-value of pre-test and post-test of both experimental and control groups. The t-test was used to know whether there was a significant difference between experimental and control group, the used of t-table was as a comparison if the result of the t-test was higher it means that there was significant difference between two groups meanwhile if the t-test was lower than the result of the t-table means that there was no significant difference between two groups. So the result of the t-test should be higher than t-table on the level of significance of 0.05 or 5% with the degree of freedom 40. The result of the t-value of post-test of both experimental and control groups was 3.36 then it was compared with the t-table on the level of significance of 0.05 or 5% with the degree of freedom 40 was 2.021. From the result above the t-value of post-test of both experimental and control groups was higher than t-table, it can be concluded that there was a significant difference between experimental and control group. The data above showed that picture series give significant effect in experimental group scores, writing procedure text through picture series could improve students’ writing procedure text ability. There were some factors that improve students’ writing ability who were taught by using picture series. First, picture series was easy to use so they could write with picture series easily, as stated by Betty (1994) that a student with a creative imagination will often learn a new language easily and enjoyable trough the use of picture while he finds it difficult to learn just from a textbook or dictionary. Second, writing procedure through picture series brought the students to new kind of situation. It would help both the teacher and students to revise the students’ writing and made writing more fun than the way it used to be, it would help the students to get ideas more realistic in understanding the procedure text and in constructing ideas to create it. That fact is similar to Betty (1994) observation that pictures enrich the classroom by bringing the topics from outside world, which are made real and immediate by the pictures. CONCLUSION The result of this study showed that there is a significant difference between the students who have been taught procedure text by using picture series and those who have not been taught by using picture series. The alternative hypothesis which said that there is a significant difference between the students who have been taught using picture series and those who have not been taught by using picture series, is acceptable. Next, there were some factors that improve student's writing ability who were taught by using picture series. First, picture series was easy to use so they could write with picture series easily. Second, writing procedure through picture series brought the students to new kind of situation. It would help both the teacher and students to revise the students’ writing and made writing more fun than the way it used to be. REFERENCES Bowen, Betty Morgan. 1995. Look Here! Visual Aids in Language Teaching. London: Modern English Publication. Brown, H. D. (2007). Principle of Language Learning and Teaching, Fifth Edition. New York: A Pearson Education Company. Chastain, K. 1988. Developing Second- language Skills: Theory to Practice. Chicago: Rand Mcwally. Degeng S., Nyoman. 2001. Media Pembelajaran, Menuju Pribadi Unggul Lewat perbaikan Kualitas Pembelajaran di Perguruan Tinggi, Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang Depdiknas. (2003). Standar Kompetensi Mata Pelajaran Bahasa Inggris untuk SMA dan MA. Jakarta: Depdiknas. Donn Bryne. 1991. Teaching Writing Skill. London: Longman Group Ltd. Fellag, L.R. 2004. Write Ahead: Skills for Academic Success. New York: Longman Finnochiaro, Marry. 1974. English as Second Language from Theory to Practice. Regent Publishing Co: New York. Hyland, Ken. 2003. Second Language Writing. UK: Cambridge University Press. Myles, J. 2002. Second Language Writing and Research: The Writing Process and Error Analysis in Student Texts. TESL-EJ, 6(2). Wright, Andrew. 1997. Pictures for Language Learning. Cambridge: Cambridge University Press.